Electromagnetic waveguide with EMI shielding gasket
By using a combination of self-supporting bodies of nonwoven carbon nanotubes and other materials, the problem of insufficient shielding effect of existing EMI shielding pads in extremely wide bands is solved, and an efficient electromagnetic interference shielding effect is achieved, which is suitable for multi-band applications.
Patent Information
- Application Number
- CN202080075860.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-09
- Filing Date
- 2020-09-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-09-08
AI Technical Summary
The existing electromagnetic interference (EMI) shielding pads have insufficient shielding effect in extremely wide bands, and the attenuation value is not ideal at low surface density, making it difficult to meet the electromagnetic interference shielding requirements in multi-bands.
The self-supporting body of nonwoven carbon nanotubes is used as the main material of the EMI shielding pad. By adjusting its molding method and structure, one or more holes are introduced, and combined with other materials, such as polymers, their mechanical properties and shielding effects are improved by coating and impregnation.
It realizes effective electromagnetic interference shielding in extremely wide bands (MHz to 100GHz) and still has significant attenuation value at low surface density, providing a universal, cost-effective, high-end shielding solution.
Smart Images

Figure BDA0003620783770000091 
Figure BDA0003620783770000101 
Figure BDA0003620783770000102
Abstract
Description
[0001] The present invention relates to an electromagnetic waveguide comprising an electromagnetic interference shielding gasket comprising a self-supporting body of non-woven carbon nanotubes adapted to introduce one or more holes, and to the electromagnetic interference shielding gasket itself.
[0002] Waveguide gaskets are commonly used to provide effective electromagnetic interference (EMI) shielding and pressure sealing for flanges, covers and chokes. Gaskets can be made of non-conductive materials (such as neoprene) or conductive materials (such as copper) to suit the required function.
[0003] The present invention is based on the recognition that a self-supporting body of nonwoven carbon nanotubes has electromagnetic interference (EMI) shielding capabilities over an extremely wide frequency band (typically MHz to 100 GHz) and has unexpected attenuation values even at low surface densities. The ability of a self-supporting body of nonwoven carbon nanotubes to be easily shaped and elastically compressed facilitates its deployment as, for example, an effective electromagnetic interference (EMI) shielding gasket.
[0004] Viewed from a first aspect, the present invention provides an electromagnetic waveguide comprising:
[0005] a first waveguide section;
[0006] a second waveguide section;
[0007] a first flange mounted on an end of the first waveguide portion;
[0008] a second flange mounted on an end of the second waveguide portion, wherein the first flange is connected (eg, sealingly connected) to the second flange; and
[0009] an EMI shielding gasket installed between the first flange and the second flange,
[0010] The EMI shielding gasket comprises a self-supporting body of non-woven carbon nanotubes adapted to introduce one or more pores.
[0011] Under compression, the EMI shielding gasket effectively seals the joint (joint) between the first flange and the second flange. With the ability to optimize thickness, mechanical properties (through manufacturing process), shape and surface chemistry (e.g., through coating), the EMI shielding gasket is a versatile, cost-effective and high-end shielding solution for the electromagnetic waveguide of the present invention.
[0012] The self-supporting body of nonwoven carbon nanotubes can be adjusted to introduce multiple holes with the same or different shapes. The self-supporting body of nonwoven carbon nanotubes can be adjusted to introduce a single hole. The outline of the (or each) hole can be substantially circular, square or rectangular.
[0013] The self-supporting body of the non-woven carbon nanotubes may be a stack (laminate). The self-supporting body of the non-woven carbon nanotubes may be fibrous (fibrous). For example, the support of the non-woven carbon nanotubes may be a fiber, a film, a tape, a wire, a sheet, a net or a mat.
[0014] The self-supporting body of the nonwoven carbon nanotubes may be substantially planar (flat). The contour of the planar self-supporting body of the nonwoven carbon nanotubes may be complementary to (e.g., substantially matching) the contours of the first flange and the second flange. The contour of the planar self-supporting body of the nonwoven carbon nanotubes may be substantially circular, square, or rectangular.
[0015] The self-supporting body of the nonwoven carbon nanotube can be substantially annular. The annular self-supporting body of the nonwoven carbon nanotube can be substantially circular (e.g., an O-ring or a D-ring) or rectangular. The cross-section of the annular self-supporting body of the nonwoven carbon nanotube can be substantially O-shaped or D-shaped.
[0016] The annular self-supporting body of non-woven carbon nanotubes may be located in an annular recess in the connecting surface of the first flange and / or the second flange.
[0017] The self-supporting body of nonwoven carbon nanotubes can be combined with additional materials.
[0018] The additional material may be in particulate or fibrous form or a coating.
[0019] The additional material may be a polymer (eg, a conductive or non-conductive polymer), a metal, or a non-metal (eg, carbon).
[0020] The polymer may be an elastomer. The polymer may be a thermoplastic, thermoformable or thermosetting polymer. The thermoformable polymer may be acrylonitrile butadiene styrene (ABS). The polymer may be chemically active (e.g., polymerizable or cross-linkable).
[0021] The self-supporting body of nonwoven carbon nanotubes can be combined with the additional material by well-known techniques such as vacuum forming, lamination, spinning, weaving, winding, dispersing or bonding (eg, thermal bonding or chemical bonding or electroplating).
[0022] Preferably, the self-supporting body of non-woven carbon nanotubes is coated. Particularly preferably, the self-supporting body of non-woven carbon nanotubes is coated with a polymer (eg a conductive or non-conductive polymer).
[0023] The coating may be a complete coating or a partial coating. Preferably, the coating is a partial coating. The partial coating may be achieved using a low molecular weight polymer and advantageously leaves the nonwoven carbon nanotubes exposed.
[0024] Preferably, the polymer impregnates the self-supporting body of non-woven carbon nanotubes. This can be achieved using low molecular weight polymers and is advantageously used to improve the mechanical behavior of the self-supporting body of non-woven carbon nanotubes.
[0025] In a preferred embodiment, the polymer is polyvinylpyrrolidone (PVP). Particularly preferably, the polymer is low molecular weight PVP. An advantage of this embodiment is that PVP increases the cohesive strength of the self-supporting body of non-woven carbon nanotubes.
[0026] The polymer may be silicone.
[0027] In a preferred embodiment, the self-supporting body of non-woven carbon nanotubes is coated with a non-conductive polymer. Preferably, the non-conductive polymer is a fluorine-containing polymer. Particularly preferred is polyvinylidene fluoride (PVDF) or a copolymer or terpolymer thereof.
[0028] In a preferred embodiment, a self-supporting body of non-woven carbon nanotubes is coated with a conductive polymer.
[0029] The self-supporting body of non-woven carbon nanotubes may be coated with a mixture of one or more polymers (eg conductive or non-conductive polymers) as defined above.
[0030] The first flange and the second flange may be the same or different. Typically, the first flange and the second flange are the same. The first flange and the second flange may be contact flanges, cover flanges or choke flanges.
[0031] The connecting faces of the first flange and the second flange respectively may be substantially square, circular, octagonal or rectangular.The first flange and the second flange may include z-axis features, such as a ramp, a taper or a serration.
[0032] The first flange and the second flange may be threaded or connected with a plurality of fasteners (eg, bolts or pins).
[0033] The connection between the first flange and the second flange can be gas-tight.The connection between the first flange and the second flange can be a contact connection or a choke connection.
[0034] The first waveguide portion and the second waveguide portion may be identical or different. Typically, the first waveguide portion and the second waveguide portion are identical.
[0035] The first waveguide portion and the second waveguide portion may be elongated hollow conductive conduits (e.g., metal tubes). The first flange may be socket-mounted or thru-mounted on the first waveguide portion. The second flange may be socket-mounted or thru-mounted on the second waveguide portion.
[0036] The self-supporting body of nonwoven carbon nanotubes can be tailored to introduce one or more pores by molding or cutting (eg, laser, water, blade, air, or die cutting).
[0037] The one or more apertures may include an opening (eg, a substantially central opening) for electromagnetic radiation. The one or more apertures may include a fastening hole for receiving a fastener connecting the first flange and the second flange.
[0038] Preferably, the surface density of the self-supporting body of the nonwoven carbon nanotube is 60gsm or less. Particularly preferably, the surface density of the self-supporting body of the nonwoven carbon nanotube is 30gsm or less. More preferably, the surface density of the self-supporting body of the nonwoven carbon nanotube is 20gsm or less.
[0039] Preferably, the surface of the self-supporting body of the non-woven carbon nanotube is uneven. For example, the surface of the self-supporting body of the non-woven carbon nanotube may be curled, concave, corrugated or wavy.
[0040] Preferably, the thickness of the self-supporting body of nonwoven carbon nanotubes undergoes a variation of up to 20%.
[0041] The self-supporting body of non-woven carbon nanotubes may be provided with a polymer core. The polymer core may be an elastomeric core or a thermosetting or thermoplastic polymer core.
[0042] Preferably, the EMI shielding gasket is obtainable or obtained by a method comprising:
[0043] (a) introducing a stream of a metal catalyst or a metal catalyst precursor into a temperature-controlled flow-through reactor;
[0044] (b) introducing a stream of a carbon source into the temperature-controlled flow-through reactor;
[0045] (c) exposing a metal catalyst or metal catalyst precursor and a carbon source to a temperature zone sufficient to produce a particulate metal catalyst and produce carbon nanotubes;
[0046] (d) removing the carbon nanotubes as a continuous effluent through a discharge outlet of the temperature-controlled flow-through reactor;
[0047] (e) collecting a continuous discharge in the form of a self-supporting body of nonwoven carbon nanotubes; and
[0048] (f) modifying the self-supporting body of nonwoven carbon nanotubes to introduce one or more pores.
[0049] Typically, the particulate metal catalyst is a nanoparticulate metal catalyst. Preferably, the nanoparticles of the nanoparticulate metal catalyst have an average diameter (e.g., number, volume or surface average diameter) in the range of 1-50 nm (preferably 1-10 nm). Preferably, 80% or more of the particles of the nanoparticulate metal catalyst have a diameter of less than 30 nm. Particularly preferably, 80% or more of the particles of the nanoparticulate metal catalyst have a diameter of less than 12 nm. The concentration of the particulate metal catalyst may be 10 6 Up to 10 10 Particles cm -3 within the range.
[0050] Typically, the metal catalyst is one or more of: alkali metals, transition metals, rare earth elements (such as lanthanides) and actinides. Preferably, the metal catalyst is one or more of: transition metals, rare earth elements (such as lanthanides) and actinides.
[0051] Preferably, the metal catalyst is at least one of the following: Fe, Ru, Co, W, Cr, Mo, Rh, Ir, Os, Ni, Pd, Pt, Ru, Y, La, Ce, Mn, Pr, Nd, Tb, Dy, Ho, Er, Lu, Hf, Li and Gd.
[0052] Preferably, the metal catalyst is iron.
[0053] The metal catalyst precursor may be a metal complex or an organometallic metal compound. Examples include iron pentacarbonyl, ferrocene or a ferrocene derivative (eg ferrocene sulfide).
[0054] Preferably, the metal catalyst precursor contains sulfur. The metal catalyst precursor containing sulfur can promote the growth of carbon nanotubes.
[0055] Preferably, the metal catalyst precursor is a sulfur-containing organometallic type. Particularly preferably, the metal catalyst precursor is a sulfur-containing iron organometallic type. More preferably, the metal catalyst precursor is a sulfur-containing ferrocene derivative. Still more preferably, the metal catalyst precursor is mono-(methylthio)ferrocene or bis-(methylthio)ferrocene.
[0056] The flow rate of the metal catalyst or metal catalyst precursor may be in the range of 1 to 50 g / hour (eg, about 7 g / hour).
[0057] The metal catalyst or metal catalyst precursor may be introduced in step (a) together with a sulfur-containing additive. The sulfur-containing additive may promote the growth of carbon nanotubes. The sulfur-containing additive may be thiophene, iron sulfide, a sulfur-containing ferrocene derivative (e.g., ferrocene sulfide), hydrogen sulfide, or carbon disulfide.
[0058] In a preferred embodiment, the sulfur-containing additive is thiophene or carbon disulfide. Particularly preferably, the sulfur-containing additive is thiophene.
[0059] In a preferred embodiment, the metal catalyst precursor is ferrocene, optionally together with a sulfur-containing additive, preferably thiophene or carbon disulfide.
[0060] The flow rate of the sulfur-containing additive may be in the range of 0.1 to 10 g / hour (eg, about 5 g / hour).
[0061] The metal catalyst or metal catalyst precursor introduced in step (a) may be in gaseous, liquid or solid form. The metal catalyst or metal catalyst precursor may be introduced in step (a) together with a non-metallic catalyst modifier or its precursor. The non-metallic catalyst modifier may be chalcogen-containing (e.g., sulfur-containing).
[0062] The generation of the particulate metal catalyst may be initiated in step (c) by thermal decomposition or dissociation of the metal catalyst or metal catalyst precursor into metal species (e.g., atoms, free radicals, or ions). The generation of the particulate metal catalyst in step (c) may include nucleation of the metal species into nucleated metal species (e.g., clusters). The generation of the particulate metal catalyst may include growth of the nucleated metal species into the particulate metal catalyst.
[0063] The metal catalyst or metal catalyst precursor may be introduced (eg injected) in step (a) in a linear, axial, vortex, spiral, laminar or turbulent flow path. The metal catalyst or metal catalyst precursor may be introduced at a variety of locations.
[0064] In step (a), the metal catalyst or metal catalyst precursor may be introduced axially or radially into the temperature-controlled flow-through reactor. The metal catalyst or metal catalyst precursor may be introduced axially via a probe or a syringe.
[0065] The metal catalyst or metal catalyst precursor may be mixed with a carrier gas. The carrier gas is typically one or more of the following: nitrogen, argon, helium or hydrogen. The mass flow rate of the metal catalyst or metal catalyst precursor mixed with the carrier gas is usually in the range of 10 to 30 lpm.
[0066] Prior to step (b), the carbon source may be heated.
[0067] Prior to step (b), the carbon source may be subjected to radiative heat transfer via an infrared, visible, ultraviolet or X-ray energy source.
[0068] In step (b), the carbon source may be introduced (eg, injected) in a linear, axial, vortex, spiral, laminar, or turbulent flow path.
[0069] In step (b), the carbon source may be introduced axially or radially into the temperature controlled flow-through reactor. The carbon source may be introduced axially via a probe or a syringe. The carbon source may be introduced at a variety of locations.
[0070] The carbon source may be an optionally substituted and / or optionally hydroxylated aromatic or aliphatic acyclic or cyclic hydrocarbon (e.g. alkyne, alkane or alkene), which is optionally interrupted by one or more heteroatoms (e.g. oxygen). Preferred are optionally halogenated C 1-6 hydrocarbons (e.g. methane, propane, ethylene, acetylene or tetrachloroethylene), optionally mono-, di- or tri-substituted benzene derivatives (e.g. toluene) or C 1-6 Alcohol (eg ethanol).
[0071] Preferably, the carbon source is methane, optionally (but preferably) in the presence of optionally substituted and / or optionally hydroxylated aromatic or aliphatic acyclic or cyclic hydrocarbons (e.g. alkynes, alkanes or alkenes), which are optionally interrupted by one or more heteroatoms (e.g. oxygen).
[0072] The carbon source can be C 1-6 Hydrocarbons such as methane, ethylene or acetylene.
[0073] The carbon source may be an alcohol such as ethanol or butanol.
[0074] The carbon source may be an aromatic hydrocarbon such as benzene or toluene.
[0075] In a preferred embodiment, the carbon source is methane, optionally in the presence of propane or acetylene.
[0076] The flow rate of the carbon source may be in the range of 50 to 30,000 sccm (eg, 2,000 sccm).
[0077] Typically in step (b) the carbon source is introduced together with a carrier gas such as helium, hydrogen, nitrogen or argon.
[0078] The flow rate of the carrier gas may be in the range of 1000 to 50000 sccm (eg, 30000 sccm).
[0079] In a preferred embodiment, steps (a) and (b) are performed simultaneously. For this purpose, the metal catalyst or metal catalyst precursor is preferably suspended or dissolved in a carbon source. Particularly preferably, the metal catalyst or metal catalyst precursor and the sulfur-containing additive are suspended or dissolved in a carbon source. For example, ferrocene and thiophene can be dissolved in an organic solvent such as butanol, ethanol, benzene or toluene, and the solution can be introduced (e.g., injected) into a temperature-controlled flow-through reactor.
[0080] The carbon nanotubes may be single-walled and / or multi-walled carbon nanotubes. In step (c), the carbon nanotube structure may take the form of a 3D continuous network (eg, an aerogel).
[0081] The temperature-controlled flow-through reactor may be cylindrical or of other geometric shape. The temperature-controlled flow-through reactor may be substantially vertical or horizontal. Preferably, the temperature-controlled flow-through reactor is substantially horizontal.
[0082] The walls of the temperature-controlled flow-through reactor may be selectively cooled by exposure to a cooling fluid such as water, liquid nitrogen, or liquid helium.
[0083] The temperature-controlled flow-through reactor can be adjusted to provide an axial temperature gradient. The axial temperature gradient can be non-uniform (e.g., stepped). The temperature of the temperature-controlled flow-through reactor can be controlled by resistive heating, plasma, or laser.
[0084] Preferably, the temperature profile in the temperature-controlled flow-through reactor is substantially parabolic.
[0085] The temperature zone sufficient to produce the particulate metal catalyst and to produce carbon nanotubes may extend over a range of at least 600 to 1500°C.
[0086] The temperature-controlled flow-through reactor can be adapted to introduce reactants through an injection nozzle, lance, probe, or multi-orifice injector (eg, sparger injector).
[0087] Step (d) may be performed by mechanical force, electrostatic force or magnetic force.
[0088] Step (e) can be performed mechanically. For example, step (e) can be performed on a rotating mandrel or drum.
[0089] The method can also include cutting, chopping, shaping, laying, flattening, stretching, unfolding, aligning, combing, heating, vibrating, or reinforcing the self-supporting body of nonwoven carbon nanotubes.
[0090] The method may further include chemically conditioning the self-supporting body of nonwoven carbon nanotubes.
[0091] The method may further comprise densifying the self-supporting body of nonwoven carbon nanotubes. Typically, densification is followed by air drying.
[0092] The method may further include coating the self-supporting body of nonwoven carbon nanotubes.
[0093] Preferably, the conductivity of the self-supporting body of nonwoven carbon nanotubes is between 10 3 Up to 10 6 S / m, particularly preferably in the range of 10000 to 500000 S / m.
[0094] The areal density of the self-supporting body of nonwoven carbon nanotubes can be varied by varying the duration of step (e).
[0095] Viewed from another aspect the invention provides an EMI shielding gasket as hereinbefore defined.
[0096] Viewed from yet another aspect the invention provides the use of a self-supporting body of non-woven carbon nanotubes as hereinbefore defined for EMI (eg RFI) shielding.
[0097] The use of the self-supporting body of nonwoven carbon nanotubes for EMI shielding is preferably as or for a shielding gasket, a shielding housing, a shielding can, a shielding card, a shielding backplane, a shielding chamber, a shielding tape or a shielding cable.
[0098] The present invention will now be described in a non-limiting sense with reference to the accompanying drawings, in which:
[0099] Figures 1 to 32 is an attenuation graph showing the shielding performance of a representative embodiment of an EMI shielding gasket according to the present invention;
[0100] Fig.33 and 34 SEM images showing uncoated and coated CNT materials;
[0101] Fig.36 A comparison of tensile stress and strain (%) is shown for uncoated and coated CNT materials;
[0102] Fig.37 A comparison of the fracture energies for uncoated and coated CNT materials is shown;
[0103] Fig.38 and 39 shows the test setup for Example 3 described below; and
[0104] Figures 40 to 47 Shown are the shielding performance of various gasket materials measured using the described test setup.
[0105] Example 1
[0106] The shielding performance of representative embodiments of EMI shielding gaskets according to the present invention was evaluated at high frequencies by measuring attenuation relative to free space or a polyethylene (PE) spacer.
[0107] experiment
[0108] The measurements were performed using a horn antenna placed at a fixed distance to the flange side of the waveguide. The signal source generated the test signal. The following flanges (Flann Microwave Limited) and frequencies were used:
[0109] WR-112 10GHz
[0110] WR-42 26.5GHz
[0111] WR-19 50GHz.
[0112] The WR-112 is a choke flange that has better metal-to-metal performance than a standard flange. For the WR-112, the source is enclosed in a screen box.
[0113] For the WR-42 and WR-19, the source is in the waveguide.
[0114] The termination in each case is a waveguide load. The test method is based on IEEE Std 299:2006, and the test equipment is listed in Table 1.
[0115] Table 1
[0116] Item Number model illustrate Manufacturer H058 861D 40-60GHz Horn Antenna 25dBi Alpha E204 45821H 26-40GHz Horn Antenna 20dBi Hughes E329 8349B 2-20GHz Amplifier Agilent E296-4 11970U 40-60GHz mixer Agilent E366 WBH224S 1.7-24GHz Horn Antenna Q-par E777 MG3695B 50GHz Signal Generator Anritsu E755 N9030B PXA Spectrum Analyzer Keysight E853 - Cable 2.4 / 2.92mm E933 321B WR-112 Load Narda Calstron E934 U910A WR-42 Load Fmi E935 2217 WR-19 Load HP H024 ESG-0015 250kHz-15GHz Signal Generator ERA Instruments
[0117] The CNT materials used to prepare the EMI shielding gaskets of the present invention are available from TorTech under the following catalog numbers:
[0118] C-322-H3 20gsm
[0119] C-340-H3B 30gsm
[0120] C-254-H2A 60gsm.
[0121] The CNT material was laser cut according to standard techniques to introduce holes and the desired EMI shielding pad configuration. Uncoated EMI shielding pads made of CNT material and PVDF coated EMI shielding pads made of CNT material were tested. The PVDF coated EMI shielding pad was prepared by dissolving PVDF pellets (Sigma Aldrich) in acetone (15% w / w) and applying the solution to the surface of the uncoated EMI shielding pad. The acetone was evaporated to leave the PVDF coating.
[0122] A silicone elastomer containing nickel and graphite (CEM-NC001-0-0.3 80H 600 gsm) was used as a control material.
[0123] result
[0124] Figures 1 to 32 Attenuation graphs are provided in . The results are tabulated below for each waveguide type. In the attenuation graphs and tables, the following abbreviations are used:
[0125] "PVDF" is PVDF coated EMI shielding gasket
[0126] "ASIS" is an uncoated EMI shielding gasket
[0127] 'Direct' is a waveguide without a gasket (i.e. metal-to-metal contact between waveguide flanges)
[0128] "PE70" is polyethylene spacer
[0129] "NiGrSi" is a pad made of a control material.
[0130] Table 2-10GHz
[0131]
[0132] Table 3-26.5GHz
[0133]
[0134] Table 4-50GHz
[0135]
[0136] in conclusion
[0137] The results generally show that EMI shielding gaskets made from CNT materials provide improvements in attenuation relative to gaskets made from control materials. Surprisingly, gaskets made from CNT materials with the lowest areal density (20 gsm) outperform EMI shielding gaskets made from other CNT materials (30 gsm and 60 gsm). PVDF-coated EMI shielding gaskets unexpectedly outperform the other gaskets.
[0138] Example 2
[0139] Various properties of the coated CNT materials were measured using standard techniques.
[0140] Fig.33 and 34 SEM images of each side of the CNT material (20 gsm) coated with PVP are shown separately. Fig.35 Shown is an SEM image of a CNT material coated with 10 wt% PVDF.
[0141] Fig.36 A comparison of tensile stress and strain (%) is shown for an uncoated CNT material (60 gsm), a CNT material coated with PVP (60 gsm), an uncoated CNT material (20 gsm), and a CNT material coated with PVP (20 gsm).
[0142] Fig.37A comparison of the energy to break is shown for an uncoated CNT material (60 gsm), a CNT material coated with PVP (60 gsm), an uncoated CNT material (20 gsm), and a CNT material coated with PVP (20 gsm).
[0143] Example 3
[0144] experiment
[0145] The test equipment used for the measurements is as follows:
[0146] RN Number model illustrate Manufacturer E366 WBH224S 1.7-24GHz Horn Antenna Qpar E777 MG3695B 50GHz Signal Generator Anritsu H301 45821H 24-40GHz Horn Antenna Hughes H302 DP241 6-40(50)GHz DP Speaker Fmi H304 83050A 2GHz-50GHz Amplifier Agilent H305 87421A power supply Agilent E755 N9030B PXA 3Hz-50GHz Spectrum Analyzer Keysight E759 MX6-10-NH 75-110GHZ x6 Multiplier MMW Group E781 MX4-10-NH 50-75GHz x4 Multiplier MMW Group E296-5 11970V 50-75GHZ mixer HP E296-6 11970W 75-110GHZ mixer HP E503 25240-20 20dB standard gain speaker 50-75G fmi 0410 2524-20 20dB standard gain speaker 50-75G fmi E579 27240-20 20dB standard gain speaker 75-110G fmi 0411 2724-20 20dB standard gain speaker 75-110G fmi
[0147] The test enclosure used for the testing was manufactured by Shielding Solutions Ltd based on design input from RN Electronics Ltd. It was specifically configured for testing the shielding effectiveness of materials at high frequencies (>5 GHz).
[0148] Test method:
[0149] Based on IEEE 299:2006
[0150] Test standard:
[0151] IEEE 299:2006
[0152] Test Items:
[0153] Gasket samples
[0154] Location:
[0155] Test Area A
[0156] Sample planning:
[0157] Measured at a fixed distance of 30cm, 25-100GHz
[0158] Test requirements:
[0159] Nonwoven CNT mat 25-100 GHz measurements
[0160] The effectiveness of a material relative to free space.
[0161] The main purpose of this test is to compare and evaluate the shielding performance of various gasket materials at high frequencies. These types of materials are typically used to shield small electronic enclosures, and the purpose of the test is to evaluate the suitability of each material for use in equipment that operates at these high frequencies. The materials (CNT materials manufactured by TorTech) are listed below.
[0162] MFS-NCRS001 Copper-plated Nickel on Metallized Polyester Ripstop Fabric
[0163] C-267-H3B CNT Mat 11gsm
[0164] C-279-H3B CNT mat 30gsmC-279-H3B o CNT mat 30gsm
[0165] C-302-H2 60gsm
[0166] C-314-H2 PCU 900NM 19gsm
[0167] C-283-H3 36gsm
[0168] C-283-H3 100% epoxy ring
[0169] Optiveil 20444A Copper + Nickel Coated Carbon Overlay 20gsm
[0170] Aluminum foil 40u 108gsm (for comparison at 25-50GHz)
[0171] Ground aluminum disk 10 mm thick (for comparison at 50-100 GHz)
[0172] Each spacer disk is placed centrally over a 40 mm diameter hole in the front face of the test housing (see Fig.38 ), where the frequency source is located internally (see Fig.39 ). The pads were secured by a 50 mm diameter, 10 mm thick Tufnell disc. A single toggle clamp, electrically insulated from the disc, was used to compress the pads. This ensured that the only electrical connection between the disc and the housing was provided by the pads. All pad samples were subjected to the same test procedure.
[0173] result
[0174] Figure 40-47 The shielding attenuation results (in dB) relative to free space for each gasket type measured through a 50 mm circular hole in the test fixture / shielding box and the accompanying figures are shown in FIG.
[0175] CNT materials also show promise for use as EMI shielding gasket materials, as evidenced by how well they self-terminated on the aluminum surface of housing holes.
Claims
1. Electromagnetic waveguide, including: a first waveguide section; a second waveguide section; a first flange mounted on an end of the first waveguide portion; a second flange mounted on an end of the second waveguide portion, wherein the first flange is connected to the second flange; and an EMI shielding gasket mounted between the first flange and the second flange, The EMI shielding gasket comprises a self-supporting body of non-woven carbon nanotubes adapted to introduce one or more pores.
2. The electromagnetic waveguide of claim 1, wherein the self-supporting body of non-woven carbon nanotubes is coated.
3. An electromagnetic waveguide as claimed in claim 2, wherein the coating is a partial coating.
4. An electromagnetic waveguide as claimed in claim 2 or 3, wherein the coating is a self-supporting body impregnated with non-woven carbon nanotubes.
5. The electromagnetic waveguide of any one of claims 1 to 3, wherein the self-supporting body of non-woven carbon nanotubes is coated with a polymer.
6. The electromagnetic waveguide of claim 5, wherein the polymer is a non-conductive polymer.
7. The electromagnetic waveguide of claim 6, wherein the non-conductive polymer is a fluoropolymer.
8. An electromagnetic waveguide as claimed in claim 6 or 7, wherein the non-conductive polymer is polyvinylidene fluoride (PVDF) or a copolymer or terpolymer thereof.
9. The electromagnetic waveguide of claim 5, wherein the polymer is a conductive polymer.
10. The electromagnetic waveguide of claim 5, wherein the polymer is polyvinyl pyrrolidone (PVP).
11. The electromagnetic waveguide according to any one of claims 1 to 3, wherein the area density of the self-supporting body of the non-woven carbon nanotube is 60 gsm or less.
12. The electromagnetic waveguide according to any one of claims 1 to 3, wherein the area density of the self-supporting body of the non-woven carbon nanotube is 20 gsm or less.
13. The electromagnetic waveguide according to any one of claims 1 to 3, wherein the surface of the self-supporting body of non-woven carbon nanotubes is non-uniform.
14. The electromagnetic waveguide of any one of claims 1 to 3, wherein the thickness of the self-supporting body of non-woven carbon nanotubes undergoes a variation of up to 20%.
15. An electromagnetic waveguide as claimed in any one of claims 1 to 3 obtainable or obtained by a method comprising: (a) introducing a stream of a metal catalyst or a metal catalyst precursor into a temperature-controlled flow-through reactor; (b) introducing a stream of a carbon source into the temperature-controlled flow-through reactor; (c) exposing a metal catalyst or metal catalyst precursor and a carbon source to a temperature zone sufficient to produce a particulate metal catalyst and produce carbon nanotubes; (d) removing the carbon nanotubes as a continuous effluent through a discharge outlet of the temperature-controlled flow-through reactor; (e) collecting a continuous discharge in the form of a self-supporting body of nonwoven carbon nanotubes; and (f) modifying the self-supporting body of nonwoven carbon nanotubes to introduce one or more pores.